Curva de phillips y la tasa natural de desempleo - Pérez Suárez, Víctor Benigno (2011)
This paper tries to explain, through a Phillips curve (in a bivariate simple model), the relationship between: inflation and unemployment in the Peruvian case. In addition, it presents the natural rate of unemployment for the last 19 years, and shows evidence for the fulfillment of the Phillips curve. Empirical evidence of the Lucas’ critique is shown; due to the fact that the estimate does not take into account the impacts of changes in the economic policy. The results are compared in the conclusions by assuming adaptive expectations. Moreover, the study displays a negative relationship between unemployment rate and the change in the inflation rate. Finally, it indicates that the national unemployment rate is below the natural rate of unemployment, which shows some evidence of possible inflationary pressures.